2019
DOI: 10.1002/bio.3639
|View full text |Cite
|
Sign up to set email alerts
|

Binding interaction study on human serum albumin with bactericidal gold nanoparticles synthesized from a leaf extract of Musa balbisiana: a multispectroscopic approach

Abstract: This study describes the eco-friendly, low-cost and room-temperature synthesis of gold nanoparticles from Musa balbisiana leaf extract, which acts as both reducing and stabilizing agent, and characterized by ultraviolet−visible (UV-vis) light spectroscopy, fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FE-SEM), analytical transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDAX) and dynamic light scattering (DLS) instruments. These nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…For example, it was employed to study the PC formation of human serum albumin on eco-friendly AuNPs synthesized using aqueous leaf extracts from therapeutic plant Nymphaea nouchali or Musa balbisiana. 99,100 In a different work, the deposition of BSA on Au NPs was followed. 101 The analysis of Stern−Volmer plots for the interaction of glycosylated human transferrin and nonglycosylated recombinant human transferrin with Au NPs also confirmed that these proteins form stable complexes with NPs and the fluorescence is quenched following the static mechanism.…”
Section: K Pmentioning
confidence: 99%
“…For example, it was employed to study the PC formation of human serum albumin on eco-friendly AuNPs synthesized using aqueous leaf extracts from therapeutic plant Nymphaea nouchali or Musa balbisiana. 99,100 In a different work, the deposition of BSA on Au NPs was followed. 101 The analysis of Stern−Volmer plots for the interaction of glycosylated human transferrin and nonglycosylated recombinant human transferrin with Au NPs also confirmed that these proteins form stable complexes with NPs and the fluorescence is quenched following the static mechanism.…”
Section: K Pmentioning
confidence: 99%
“…54 Again "peak-2" at λ excitation = 230 and λ emission = 341 indicates the polypeptide backbone structures of BSA. 53 Both "peak-1" and "peak-2" of BSA decrease with one time addition of 10 μM complexes (Pt-1−Pt-4). The decrease of intensity indicates the conformational changes of the polypeptide backbone structure of BSA, which is due to a change in the microenvironment at the vicinity of either or both tryptophan and tyrosine residues.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[ 36 ] Several investigations on the interaction of small molecules and drugs to HSA have been recently published. [ 37–42 ] To the best of our knowledge, no previous research has been published on the intermolecular binding interactions of EPL with serum albumin using several spectroscopic and molecular docking approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Several investigations on the interaction of small molecules and drugs to HSA have been recently published. [37][38][39][40][41][42] To the best of our Standard stock solution of HSA (2.0 μM) was freshly prepared and obtained by weighing 0.0133 g of HSA and then dissolving in distilled water in a volumetric flask (100 ml). The 20.0 mM Trishydrochloric acid (HCl) buffer (pH 7.4) was obtained by weighing 0.24 g of Tris and dissolving it in distilled water in a volumetric flask (100 mL).…”
mentioning
confidence: 99%